Preparation method of fast-charging artificial graphite negative electrode material

By performing component cutting and pyrolysis treatment of heavy oil raw materials, combined with thermal polymerization and crosslinking reactions, fast charging artificial graphite negative electrode materials are prepared, which solves the problems of lithium extraction phenomenon and complex preparation process in the prior art, and achieves efficient and safe fast charging performance.

CN119954150AActive Publication Date: 2025-05-09PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311472108.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2025-05-09
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

The artificial graphite materials used in existing fast-charging lithium batteries are prone to lithium extraction when charging at large-scale, which affects the safety of the battery cell. The preparation process is complex, the cost is high, and the fast-charging performance is limited.

Method used

By cleaving the heavy oil raw material in components, heavy component A and light component A1 are obtained, and pyrolyzed, separated and washed, to obtain a carbonaceous mesophase material and isotropic aromatic hydrocarbon solution. Then, a coating agent is prepared by thermal polymerization and crosslinking reaction, and combined with the surface modification treatment of pulverization and modifier, and finally, a fast-charge artificial graphite negative electrode material is prepared by high-temperature carbonization and graphitization treatment.

Benefits of technology

It realizes excellent performance and good cycle performance of lithium-ion batteries under fast charging conditions, reduces preparation costs, simplifies process flow, and improves the safety and fast charging performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954150A_ABST
    Figure CN119954150A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a fast-charging artificial graphite negative electrode material, which comprises the following steps: carrying out component cutting, pyrolysis, separation and washing on a specific petroleum raw material to obtain a carbonaceous intermediate phase material, and carrying out thermal polymerization and cross-linking reaction on light components to obtain a coating agent, so that the use of a catalyst is reduced; various components of an aromatic hydrocarbon raw material are fully utilized to realize integrated development of a graphite raw material, and the artificial graphite negative electrode material is obtained through crushing, surface modification treatment under the action of a specific modifier, carbonization, heat treatment, graphitization and re-coating. And the preparation process is simple, low in cost and suitable for high-capacity fast-charging lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of artificial graphite negative electrode materials, and in particular relates to a method for preparing a fast-charging artificial graphite negative electrode material. Background Art

[0002] With the development of new energy power batteries, the improvement of material performance has gradually met the requirements of long battery life. However, during use, people also hope to be able to complete 50% of the power replenishment in a short time, such as 20 to 30 minutes. The demand for fast-charging batteries is getting higher and higher, so fast-charging negative electrode materials are needed to match. When lithium-ion batteries are charged, lithium migrates to the negative electrode. The excessive potential caused by the large current of fast charging will cause the negative electrode potential to be more negative. At this time, the pressure of the negative electrode to quickly accept lithium will increase, and the tendency to generate lithium dendrites will increase. Therefore, during fast charging, the negative electrode must not only meet the kinetic requirements of lithium diffusion, but also solve the safety problems caused by the increased tendency of lithium dendrite generation. Therefore, the main technical difficulty of fast charging cells is actually the embedding of lithium ions in the negative electrode. At present, many graphite materials on the market are prone to lithium precipitation on the surface of the negative electrode when charged at a high rate, which has a great impact on the safety of the battery cell. The embedding reaction of lithium in artificial graphite materials has a strong directionality, so the main direction of graphite surface treatment, improving its structural stability, and promoting the diffusion of lithium ions on the base is the main direction that needs to be worked on.

[0003] CN112289986A spheroidizes and shapes one or more of needle coke, petroleum coke, and pitch coke after rough crushing and fine grinding, and then mixes with a first carbon source, first heats for surface coating, then carbonizes at high temperature, and then performs high-temperature graphitization to obtain artificial graphite powder; then mixes the obtained artificial graphite powder with a second carbon source, first heats for surface coating, and then carbonizes at high temperature to obtain a high-rate fast-charging graphite negative electrode material. However, it is difficult to obtain a carbonaceous powder with high sphericity for raw materials such as needle coke, petroleum coke, and pitch coke due to their own physical properties.

[0004] CN111115622A is configured with a graphite precursor content of 100-150g; a binder composed of aluminum nitrate and ethanol (15-20g: 12-13g) and an asphalt liquid composed of asphalt, gasoline, kerosene, diesel and industrial benzene (18-22g: 2-5g: 1-4g: 2-5g: 3-5g), allowing the graphite precursor to be randomly distributed in the solution, and forming isotropic secondary particles after spray drying, and melting the asphalt in the secondary particles after heating and carbonization to bond the disorderly arranged precursors in the secondary particles, and preparing the product after graphitization. Due to the presence of benzene components in the solution, the flash point is low and the volatility is high, and it needs to be recycled, which has certain safety and environmental risks.

[0005] CN109748587A uses graphitized coke / high crystallinity graphite and difficult graphitized coke / hard carbon for secondary granulation, then mixes with asphalt for composite reaction, crushes after composite, and then graphitizes, and then performs modification and carbonization after graphitization. The secondary particles are used as the core and the surface is coated with a double layer. Since the difficult-graphitized materials with streamlined / fibrous structure / wide-area structure accounting for 80%-100% and mosaic structure accounting for 50%-100% need to be identified and distinguished separately, the analysis workload is heavy.

[0006] The above inventions design the fast-charging performance of artificial graphite from different angles such as the selection of raw materials, the selection of double-layer coating process, and the balling process, but fail to achieve the preparation of fast-charging artificial graphite from the design of aromatic raw material molecules and the corresponding carbonaceous intermediate phase and integrated raw materials, and the design of artificial graphite precursor modification process. There is no literature report on the improvement of the fast-charging performance of artificial graphite by using petroleum raw materials such as catalytic cracking oil slurry and ethylene tar through component cutting, purification of polycyclic aromatic components, adjustment of thermal polymerization degree, and comprehensive utilization of by-product distillate oil, combined with the preparation process of artificial graphite.

[0007] The artificial graphite materials used in existing fast-charging lithium batteries are all made from needle coke, asphalt coke, and petroleum coke. Most of them are designed for performance through coating and granulation processes. Since the raw material structure is basically finalized, it is necessary to add coating agents multiple times, which has high manufacturing costs and limited improvement in fast-charging performance. The second coating of the graphitized material can improve performance, but it prolongs the manufacturing cycle and increases manufacturing costs. Therefore, how to improve the fast-charging ability of the battery cell while ensuring safety, performance, and cost has become a problem that needs to be solved urgently. Summary of the invention

[0008] The object of the present invention is to provide a method for preparing a fast-charging artificial graphite negative electrode material, wherein the lithium-ion battery of the graphite negative electrode material has excellent fast-charging performance and good cycle performance.

[0009] To achieve the above object, the present invention provides a method for preparing a fast-charging artificial graphite negative electrode material, comprising:

[0010] S1, cutting the heavy oil raw material into components to obtain a heavy component A and a light component A1, and then removing impurities from the heavy component A to obtain a purified heavy component A;

[0011] S2, pyrolyzing the purified heavy component A under an inert atmosphere to obtain a mixed solution B containing a carbonaceous mesophase material, and separating the mixed solution B containing a carbonaceous mesophase material to obtain a carbonaceous mesophase material C and an isotropic aromatic solution D;

[0012] S3, mixing the isotropic aromatic solution D with the light component A1 and subjecting them to a thermal polymerization reaction to obtain a coating agent precursor, mixing the coating agent precursor with a cross-linking agent and a catalyst to conduct a cross-linking reaction, and subjecting the cross-linked product to a vacuum treatment to obtain a coating agent E;

[0013] S4, the carbonaceous mesophase material C is dried and crushed, then modified with a gas containing an oxygen element, and then graphitized to obtain graphite powder F;

[0014] S5, mixing the graphite powder F and the crushed coating agent E, and obtaining a fast-charging artificial graphite negative electrode material after surface treatment and high-temperature carbonization.

[0015] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the heavy oil raw material includes one or more of catalytic cracking oil slurry, ethylene tar, atmospheric residue oil and vacuum residue oil.

[0016] The preparation method of the fast-charging artificial graphite negative electrode material described in the present invention is to cut the components into distillation at 5-20 torr, the heavy component A is a fraction with a boiling point greater than 350°C; the light component A1 is a fraction with a boiling point of 200-350°C.

[0017] The method for preparing the fast-charging artificial graphite negative electrode material of the present invention, wherein the density of the heavy component A at 15°C is 0.9 g / cm 3 above, asphaltene content below 30%, preferably below 25%, saturated content below 20%, preferably below 10%, aromatics content above 50%, preferably above 70%, sulfur content below 1%, preferably below 0.5%, nitrogen content below 0.7%, preferably below 0.4%, residual carbon content 3-20%, preferably 5-15%, most preferably 7-12%.

[0018] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the asphaltene content in the purified heavy component A is less than or equal to 20%, and the ash content is less than or equal to 10 ppm.

[0019] The preparation method of the fast-charging artificial graphite negative electrode material described in the present invention, in step S2, in a heating reactor with stirring, the temperature is raised to a reaction temperature of 360-450°C, preferably 400-420°C, at a stirring rate of 50-200r / min and a heating rate of 10-30°C / min, preferably 15-25°C / min, for a pyrolysis reaction. The pyrolysis reaction time is 1-15 hours, preferably 6-8 hours. The heating method of the heating reactor can be electromagnetic, direct electric heating, tin bath, or salt bath; the feed ratio of inert gas to purified heavy component A in the pyrolysis reaction is 0.1L / 1kg-0.5L / kg.

[0020] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the thermal polymerization reaction temperature in step S3 is 250-350°C, preferably 280-320°C, the reaction time is 2-10 hours, preferably 5-7 hours, the stirring rate is 50-150r / min, preferably 80-120r / min, and the reaction pressure is 0.1-0.2Mpa.

[0021] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the cross-linking reaction temperature in step S3 is 80-180°C, preferably 100-120°C, the reaction time is 0.5-3 hours, preferably 1-2 hours, and the stirring speed is 100-300r / min, preferably 150-200r / min.

[0022] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the mass ratio of the coating agent precursor to the catalyst and the cross-linking agent in step S3 is 1000:1-4:3-10, preferably 1000:1-2:5-7, the catalyst is one of p-toluenesulfonic acid, boron trifluoride, trichloroacetic acid and sulfuric acid, preferably p-toluenesulfonic acid; the cross-linking agent is one or more of terephthalic acid, benzaldehyde, terephthalaldehyde, trioxymethylene and polyformaldehyde.

[0023] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the vacuum treatment conditions in step S3 are a vacuum degree of 0.1 to 100 Pa, preferably 0.5 to 10 Pa, and a heating temperature of 180 to 320° C., preferably 250 to 280° C.

[0024] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the drying conditions of the carbonaceous mesophase material in step S4 are drying at 80 to 150° C., preferably 90 to 120° C. for 0.1 to 2 hours, preferably 0.5 to 1 hour.

[0025] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the density of the carbonaceous intermediate phase material C after drying in step S4 is 1.36-1.4 g / cm 3 , preferably 1.37 to 1.38 g / cm 3 , volatile matter is 10-20%, ash content is less than 0.2%, preferably less than 0.1%; D50 of the crushed carbonaceous mesophase material C is 5-8um, preferably 6-7um; the softening point of the coating agent E is 100-130°C, toluene insoluble matter is 20-30%, quinoline insoluble matter is 0.1-1%, coking value is 45-55%, ash content is 0.01-0.1%, and the D50 of the crushed coating agent E is 1-5um, preferably 2-3um.

[0026] In the method for preparing the fast-charging artificial graphite negative electrode material of the present invention, the gas containing oxygen elements in step S4 is an inert gas containing water vapor or carbon dioxide, and the volume ratio of water vapor or carbon dioxide to the inert gas is 1 to 10:100, preferably 4 to 6:100, and the gas flow rate of oxygen elements during the modification process is 0.01-0.3 L / min, preferably 0.05-0.1 L / min, and the modification time is 5 to 15 hours, preferably 6 to 10 hours, and the modification temperature is 550 to 700°C, preferably 620 to 670°C, and the temperature is increased to the modification temperature at a heating rate of 1 to 10°C / min, preferably 5 to 7°C / min.

[0027] The preparation method of the fast-charging artificial graphite negative electrode material of the present invention, in step S5, during mixing, the mass ratio of graphite powder F to coating agent E is 100:1-100:10, preferably 100:5-100:8, and the mixing time is 30-60 min, preferably 40-50 min; the surface treatment conditions are: in an environment where the inert gas flow rate is 0.01-0.3 L / min, preferably 0.05-0.1 L / min, at a heating rate of 1-10°C / min, preferably 5-7°C / min, heating to 550-700°C, preferably 620-670°C, and treating for 5-15 hours, preferably 6-10 hours; the high-temperature carbonization conditions are: heating to 1000-1500°C, preferably 1200-1300°C, at a heating rate of 1-7°C / min, preferably 3-5°C / min, for carbonization treatment for 1-5 hours, preferably 2-3 hours.

[0028] Beneficial effects of the present invention:

[0029] The present invention obtains carbonaceous mesophase material by cutting, pyrolyzing, separating and washing specific petroleum raw materials, and obtains coating agent by combining thermal polymerization and cross-linking reaction of light components, thereby reducing the use of catalysts and making full use of various components of aromatic raw materials to realize the integrated development of graphite raw materials, and obtains artificial graphite negative electrode material by crushing, surface modification treatment under the action of specific modifiers, carbonization, heat treatment and graphitization and then coating again. The preparation process is simple, the cost is low, and it is suitable for high-capacity fast-charge lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a process flow chart of the method for preparing the fast-charging artificial graphite negative electrode material of the present invention. DETAILED DESCRIPTION

[0031] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0032] The process flow of the preparation method of the fast-charging artificial graphite negative electrode material of the present invention is as follows Figure 1 shown.

[0033] (1) After blending different raw materials, the components are cut into heavy component A and light component A1 through pretreatment unit 1, and then the heavy component A is impurity removed to obtain purified heavy component A; various sizes of particles and particles in the heavy component A can be removed by filtering to obtain purified heavy component A, and the filtering medium can be an inorganic membrane or a metal filter.

[0034] (2) The purified heavy component A enters the pyrolysis reaction unit 2, and an inert gas is introduced, and a pyrolysis reaction occurs under stirring to generate a mixed solution B containing a carbonaceous mesophase material. The pyrolysis reaction device is an electromagnetic heating kettle with stirring, and 2 or more heating kettles can be selected as needed to meet the use requirements. The inert gas can be nitrogen or argon, preferably nitrogen.

[0035] (3) The mixed solution B enters the separation unit 3 by gravity, and the carbonaceous mesophase material and the isotropic aromatic solution obtained by pyrolysis are separated to obtain the carbonaceous mesophase material C and the isotropic aromatic solution D respectively; the separation device is an intermittent filter with a metal mesh, and can also be a continuous bag-pulling automatic unloading centrifuge, a vertical blade filter, or a vertical disc filter. The continuous bag-pulling automatic unloading centrifuge is preferred. According to the amount of material to be processed, two or more centrifuges can be used in turn.

[0036] (4) The aromatic solution D and the light component A1 are heated by power transmission and enter the unit 4. First, the molecular weight and coking value of the system are increased under the action of polymerization heat to obtain the coating agent precursor, and then enter the cross-linking reaction device, add the cross-linking agent and catalyst, react under mild conditions, and finally remove the light component through the pressure reducing device to obtain the coating agent E; there are 2 or more thermal polymerization reactors to ensure that there are continuous materials entering the cross-linking reaction device after the thermal polymerization reaction is completed. The thermal polymerization reactor is a reactor with stirring and electromagnetic heating, and is equipped with pressure protection and a light component discharge valve to ensure the reaction pressure; the product after the polymerization reaction enters the cross-linking reaction device, and the cross-linking reactor is a reactor with stirring in a heating jacket. According to the reaction time, 2 or more reactors can be set up for use in turn. The top of the cross-linking reactor is connected to a reflux tank to recover the materials for future reactions and return them to the system to continue to participate in the reaction. After the cross-linking reaction, the materials enter the vacuum device, which can be a stainless steel scraper short-range distillation system.

[0037] (5) The carbonaceous mesophase material C obtained by the separation unit is received and intermittently transferred to a drying device, which can be a box-type dryer or a tubular dryer. After drying, crushing, and particle classification, it enters the surface modification unit 5. After the modification is completed, nitrogen is introduced for cooling, and the temperature is lowered to room temperature to obtain a modified material. Since the carbonaceous mesophase itself contains 10-20% volatile matter, a pyrolysis reaction occurs during the modification process, and a 10-30nm pyrolytic carbon layer is generated on the surface. At the same time, the oxygen-containing gas in the modification process decomposes the indeterminate carbon of the pyrolytic carbon, so that the modified material has abundant micropores with a pore size of 1-2nm, providing a rapid transmission channel for lithium ions. The modified material then enters the graphitization unit 6 to obtain graphite powder F, so that the mesophase structure is further modified and improved, providing more lithium ion reaction sites, and making the material have a higher lithium storage capacity.

[0038] (6) The graphite powder F and the powder of the coating agent E are mixed and coated, and the surface modification treatment is performed. After the treatment, an inert gas (which may be nitrogen) is introduced to cool the mixture to room temperature, and then the mixture is carbonized at high temperature and the particles are adjusted again to obtain a fast-charged artificial graphite negative electrode material. The mixer during mixing may be an eccentric mixer or a conical mixer, and the stirring method of the materials in the modification device may also be a rolling method for modification.

[0039] Battery performance test: Graphite: conductive carbon black SP: sodium carboxymethyl cellulose CMC: binder styrene butadiene rubber SBR mass ratio = 95:1.5:1.5:2 were mixed and slurried, then coated on copper foil and dried to obtain a surface density of 70g / m 2 , compacted density is 1.75g / cm 3 The pole piece is used as the working electrode, the lithium sheet is used as the counter electrode, 1 mol / L LiPF6 is used as the electrolyte, and the solvent in the electrolyte is a mixed solvent composed of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC in a volume ratio of 1:1:1, and a charge and discharge test is performed; preferably, the voltage range of the charge and discharge test is 0.005-2.0V, and the charge and discharge are performed at a rate of 0.1C. The first delithiation capacity obtained is the finished battery capacity of the soft fast-charging graphite. Test its 3C discharge capacity and calculate the rate performance 3C / 0.1C.

[0040] Embodiment 1:

[0041] Using ethylene tar as raw material, vacuum distillation is carried out at a pressure of 5 torr to obtain a light component A1 with a distillation range of 210-350°C and a heavy component with a distillation range of 350-530°C. The density of the heavy fraction at 15°C is 1.15 g / cm 3, asphaltene content 22%, saturated content 2%, aromatic content 70%. Sulfur content 0.1%, nitrogen content 0.05%, residual carbon content 16%. The heavy component is filtered through an inorganic membrane to obtain a purified heavy component with an asphaltene content of 20% and an ash content of 10ppm. The purified heavy component is added to an electromagnetic heating decomposition reactor with stirring, and N2 is introduced. The feed ratio of N2 to the purified heavy component is 0.1L / 1kg. The pyrolysis is carried out under the conditions of a heating rate of 10℃ / min, a stirring rate of 50r / min, a reaction temperature of 400℃, and a reaction time of 6hr to obtain a mixed solution containing a carbonaceous mesophase material, which enters the separation unit 3 by gravity. The separation device is a continuous bag automatic unloading centrifuge to obtain an isotropic aromatic solution and a carbonaceous mesophase material. The isotropic aromatic solution is mixed with the light component A1 of the pretreatment unit 1 and then transmitted to the polymerization reaction device by power. After the carbonaceous mesophase material is received, it is intermittently transferred to the drying device. The carbonaceous mesophase material was dried in a box dryer at 120°C for 0.5 hours. After drying, the physical properties were analyzed and the true density was 1.378 g / cm 3 , volatile matter is 15%, ash content is 0.07%.

[0042] The homosexual aromatic solution and the light component A1 are reacted in a polymerization reaction device at a temperature of 320°C, a reaction time of 2 hours, a stirring rate of 100r / min, and a reaction pressure of 0.1MPa. The product after the polymerization reaction enters a cross-linking reaction device, the cross-linking reaction temperature is 180°C, the reaction time is 0.5 hours, and the stirring rate is 170r / min. The mass ratio of the polymerization reaction material to the catalyst and the cross-linking agent is 1000:1:5, the catalyst is p-toluenesulfonic acid, and the cross-linking agent is p-phenylenediol. After the cross-linking reaction, the material enters a stainless steel scraper short-path distillation system, the vacuum degree is 10Pa, and the heating temperature is 320°C to obtain a coating agent E. The coating agent E has a softening point of 101°C, 22% toluene insolubles, 0.1% quinoline insolubles, 46% coking value, and 0.01% ash.

[0043] The dried carbonaceous mesophase material and the coating agent obtained by the short-path distillation device are respectively crushed and classified to obtain two kinds of micropowders, and the D50 of the carbonaceous mesophase micropowder is 6-7um. The micropowder of the coating agent is D504-5um. Nitrogen containing water vapor is introduced into the carbonaceous mesophase micropowder for modification. The nitrogen flow rate is 0.1L / min, the modification time is 5 hours, the heating rate is 2℃ / min, and the modification temperature is 700℃. The water vapor: nitrogen ratio is 1:100. After the modification is completed, nitrogen is introduced for cooling. The temperature is cooled to room temperature to obtain the modified material, and then the graphitized micropowder F is obtained through the graphite treatment unit 6.

[0044] After graphitization, the powder F and the coating agent E are mixed in a conical mixer, the ratio of graphite powder F to coating agent E is 100:5, the mixing time is 60min, and the powder enters the coating device, nitrogen is introduced, the nitrogen flow rate is 0.05L / min, the heating rate is 2℃ / min, the coating temperature is 680℃, the coating time is 8 hours, and nitrogen is introduced to cool down after the coating is completed. The coated material is obtained, and the temperature is raised to 1400℃ at a heating rate of 4℃ / min under nitrogen protection, and carbonization treatment is carried out for 5 hours. High-capacity fast-charging artificial graphite material is obtained by breaking up, grading and treating magnetic materials. After analysis, D50 18~19um, 0.1C first discharge capacity is 368mAh / g, the first efficiency is 95%, 3C discharge capacity is 360mAh / g, and the capacity retention rate is 97%.

[0045] Embodiment 2:

[0046] The mixed raw material of catalytic cracking oil slurry and ethylene tar (mass ratio is 2:8) is subjected to vacuum distillation at a pressure of 20 torr to obtain a light component A1 with a distillation range of 210-350°C and a heavy fraction with a distillation range of 350-520°C. The density of the heavy fraction at 15°C is 1.18 g / cm 3 , asphaltene content 19%, saturated content 4%, aromatic content 72%. Sulfur content 0.2%, nitrogen content 0.1%, residual carbon content 16%. The heavy component is filtered through an inorganic membrane to obtain a purified heavy component with an asphaltene content of 16% and an ash content of 8ppm. The purified heavy component is added to an electrically heated reactor with stirring, and N2 is introduced. The feed ratio of N2 to the purified heavy component is 0.3L / 1kg. At a heating rate of 30℃ / min, a stirring rate of 100r / min, a reaction temperature of 450℃, and a reaction time of 1hr, a mixed solution containing carbonaceous mesophase material is obtained, which enters the separation unit 3 by gravity. The separation device is a continuous bag automatic unloading centrifuge to obtain an isotropic aromatic solution and a carbonaceous mesophase material. The isotropic aromatic solution is mixed with the light component A1 of the pretreatment unit 1 and then transmitted to the polymerization reaction device by power. After the carbonaceous mesophase material is received, it is transmitted to the drying device in an intermittent manner. The carbonaceous mesophase material was dried in a box dryer at 95°C for 1 hour. After drying, the physical properties were analyzed and the true density was 1.375 g / cm 3 , volatile matter is 20%, ash content is 0.15%.

[0047] The homoaromatic solution and the light component A1 are reacted in a polymerization reaction device at a temperature of 250°C, a reaction time of 10 hours, a stirring rate of 50 r / min, and a reaction pressure of 0.1 MPa. The product after the polymerization reaction enters a cross-linking reaction device, the cross-linking reaction temperature is 80°C, the reaction time is 3 hours, and the stirring rate is 100 r / min. The mass ratio of the polymerization reaction material to the catalyst and the cross-linking agent is 1000:4:10, the catalyst is sulfuric acid, and the cross-linking agent is trioxymethylene. After the cross-linking reaction, the material enters a stainless steel scraper short-path distillation system, the vacuum degree is 0.5 Pa, the heating temperature is 250°C, and the coating agent E is obtained. The softening point of the coating agent E is 130°C, the toluene insoluble matter is 29%, the quinoline insoluble matter is 0.6%, the coking value is 53%, and the ash content is 0.06%.

[0048] The dried carbonaceous mesophase material and the coating agent obtained by the short-path distillation device are respectively crushed and classified to obtain two kinds of micropowders, and the D50 of the carbonaceous mesophase micropowder is 5-7um. The micropowder of the coating agent is D501-3um. Nitrogen containing water vapor is introduced into the carbonaceous mesophase micropowder for modification. The nitrogen flow rate is 0.01L / min, the modification time is 9 hours, the heating rate is 6℃ / min, and the modification temperature is 650℃. The water vapor: nitrogen ratio is 10:100. After the modification is completed, nitrogen is introduced for cooling. The temperature is cooled to room temperature to obtain the modified material, and then the graphitized micropowder F is obtained through the graphite treatment unit 6.

[0049] After graphitization, the powder F and the coating agent E are mixed in a conical mixer. The ratio of graphite powder F to coating agent E is 100:1. The mixing time is 30 minutes. Enter the coating device, introduce nitrogen, the nitrogen flow rate is 0.3L / min, the coating time is 6 hours, the heating rate is 7℃ / min, and the coating temperature is 550℃. After the coating is completed, nitrogen is introduced to cool down to room temperature to obtain the coated material. Under nitrogen protection, the temperature is raised to 1500℃ at a heating rate of 7℃ / min, and carbonization treatment is carried out for 3 hours. High-capacity fast-charging artificial graphite material is obtained by breaking up, grading and treating magnetic materials. After analysis, D50 5~7um, 0.1C first discharge capacity is 367mAh / g, the first efficiency is 96%, 3C discharge capacity is 363mAh / g, and the capacity retention rate is 98%.

[0050] Embodiment 3:

[0051] Using vacuum residue as raw material, vacuum distillation is carried out at a pressure of 10 torr to obtain a light fraction A1 with a distillation range of 210-350°C and a heavy fraction with a distillation range of 350-520°C. The density of the heavy fraction at 15°C is 1.13 g / cm 3The above, asphaltene content is 12%, saturated content is 15%, aromatic content is 71%. Sulfur content is 0.2%, nitrogen content is 0.1%, residual carbon content is 16%. The heavy component is passed through electrostatic adsorption filtration to obtain a purified heavy component, with an asphaltene content of 10% and an ash content of 10ppm. The purified heavy component is added to a tin bath reactor with stirring, and N2 is passed through. The feed ratio of N2 to the purified heavy component is 0.5L / 1kg. Pyrolysis is carried out under the conditions of a heating rate of 25℃ / min, a stirring rate of 200r / min, a reaction temperature of 360℃, and a reaction time of 5hr to obtain a mixed solution containing carbonaceous mesophase material, which enters the separation unit 3 by gravity. The separation device is a continuous bag automatic unloading centrifuge to obtain an isotropic aromatic solution and a carbonaceous mesophase material. The isotropic aromatic solution is mixed with the light component A1 of the pretreatment unit 1 and transmitted to the polymerization reaction device by power. After the carbonaceous mesophase material is received, it is intermittently transmitted to the drying device. The carbonaceous mesophase material was dried in a box dryer at 80°C for 2 hours. After drying, the physical properties were analyzed and the true density was 1.375 g / cm 3 , volatile matter is 13%, ash content is 0.15%.

[0052] The homoaromatic solution and the light component A1 are reacted in a polymerization reaction device at a temperature of 350°C, a reaction time of 8 hours, a stirring rate of 150r / min, and a reaction pressure of 0.2MPa. The product after the polymerization reaction enters a cross-linking reaction device, the cross-linking reaction temperature is 110°C, the reaction time is 2 hours, and the stirring rate is 300r / min. The mass ratio of the polymerization reaction material to the catalyst and the cross-linking agent is 1000:1:4, the catalyst is trichloroacetic acid, and the cross-linking agent is terephthalaldehyde. After the cross-linking reaction, the material enters a stainless steel scraper short-path distillation system, the vacuum degree is 80Pa, the heating temperature is 180°C, and the coating agent E is obtained. The softening point of the coating agent E is 128°C, the toluene insoluble matter is 28%, the quinoline insoluble matter is 0.5%, the coking value is 53%, and the ash content is 0.07%.

[0053] The dried carbonaceous mesophase material and the coating agent obtained by the short-path distillation device are respectively crushed and classified to obtain two kinds of micropowders, and the D50 of the carbonaceous mesophase micropowder is 6-8um. The micropowder of the coating agent is D501-3um. Nitrogen containing carbon dioxide is introduced into the carbonaceous mesophase micropowder for modification. The nitrogen flow rate is 0.3L / min, the modification time is 15 hours, the heating rate is 10℃ / min, and the modification temperature is 550℃. Carbon dioxide gas: nitrogen 5:100, after the modification is completed, nitrogen is introduced for cooling, cooled to room temperature, and the modified material is obtained, and then the graphitized micropowder F is obtained through the graphite treatment unit 6.

[0054] After graphitization, the powder F and the coating agent E are mixed in an eccentric mixer. The ratio of graphite powder F to coating agent E is 100:8. The mixing time is 30 minutes. The powder enters the coating device and nitrogen is introduced. The nitrogen flow rate is 0.2L / min. The coating time is 15 hours, the heating rate is 10℃ / min, and the coating temperature is 650℃. After the coating is completed, nitrogen is introduced to cool it down to room temperature to obtain the coated material. Under nitrogen protection, the temperature is increased to 1000℃ at a heating rate of 1℃ / min, and carbonization treatment is carried out for 2 hours. High-capacity fast-charging artificial graphite material is obtained by breaking up, grading and treating magnetic materials. After analysis, D50 15~18um, 0.1C first discharge capacity is 366mAh / g, the first efficiency is 96%, 3C discharge capacity is 362mAh / g, and capacity retention rate is 98%.

[0055] Comparative Example 1:

[0056] Using vacuum residue as raw material, vacuum distillation is carried out at a pressure of 10 torr to obtain a light fraction A1 with a distillation range of 210-350°C and a heavy fraction with a distillation range of 350-520°C. The density of the heavy fraction at 15°C is 1.13 g / cm 3 The above, asphaltene content is 12%, saturated content is 15%, aromatic content is 71%. Sulfur content is 0.2%, nitrogen content is 0.1%, residual carbon content is 16%. The heavy component is added to a tin bath reactor with stirring, N2 is introduced, the feed ratio of N2 to purified heavy component is 0.5L / 1kg, and pyrolysis is carried out under the conditions of heating rate of 25℃ / min, stirring rate of 200r / min, reaction temperature of 360℃, and reaction time of 5hr to obtain a mixed solution containing carbonaceous mesophase material, which enters the separation unit 3 by gravity. The separation device is a continuous bag automatic unloading centrifuge to obtain isotropic aromatic solution and carbonaceous mesophase material. The isotropic aromatic solution is mixed with the light component A1 of the pretreatment unit 1 and then transmitted to the polymerization reaction device by power. After the carbonaceous mesophase material is received, it is transferred to the drying device in an intermittent manner. The carbonaceous mesophase material is dried at 80℃ and the drying time is 2 hours in a box dryer. After drying, the physical properties were analyzed and the true density was 1.376 g / cm 3 , volatile matter is 13%, ash content is 0.3%.

[0057] The dried carbonaceous mesophase material and the coating agent purchased from the market (the coating agent has a softening point of 220°C, 20% toluene insoluble matter, 0.5% quinoline insoluble matter, 65% coking value, and 0.06% ash) are crushed and classified by a pulverizing device to obtain two kinds of micropowders. The micropowder D50 of the carbonaceous mesophase is 6 to 8 um. The micropowder of the coating agent is D502 to 3 um. The micropowder of the carbonaceous mesophase is passed through a graphite processing unit 6 to obtain graphitized micropowder F.

[0058] After graphitization, the powder F and the coating agent are mixed in a conical mixer. The ratio of graphite powder F to coating agent E is 100:8. The mixing time is 30 minutes. The powder enters the coating device and nitrogen is introduced. The nitrogen flow rate is 0.2L / min. The coating time is 15 hours, the heating rate is 10℃ / min, and the coating temperature is 650℃. After the coating is completed, nitrogen is introduced to cool it down to room temperature to obtain the coated material. Under nitrogen protection, the temperature is increased to 1000℃ at a heating rate of 1℃ / min, and carbonization treatment is carried out for 2 hours. High-capacity fast-charging artificial graphite material is obtained by breaking up, grading and treating magnetic materials. After analysis, D50 13~16um, 0.1C first discharge capacity is 348mAh / g, the first efficiency is 95%, 3C discharge capacity is 262mAh / g, and capacity retention rate is 75%.

[0059] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a fast-charging artificial graphite negative electrode material, characterized in that: include: S1, cutting the heavy oil raw material into components to obtain a heavy component A and a light component A1, and then removing impurities from the heavy component A to obtain a purified heavy component A; S2, pyrolyzing the purified heavy component A under an inert atmosphere to obtain a mixed solution B containing a carbonaceous mesophase material, and separating the mixed solution B containing a carbonaceous mesophase material to obtain a carbonaceous mesophase material C and an isotropic aromatic solution D; S3, mixing the isotropic aromatic solution D with the light component A1 and subjecting them to a thermal polymerization reaction to obtain a coating agent precursor, mixing the coating agent precursor with a cross-linking agent and a catalyst to conduct a cross-linking reaction, and subjecting the cross-linked product to a vacuum treatment to obtain a coating agent E; S4, the carbonaceous mesophase material C is dried and crushed, then modified with a gas containing an oxygen element, and then graphitized to obtain graphite powder F; S5, mixing the graphite powder F and the crushed coating agent E, and obtaining a fast-charging artificial graphite negative electrode material after surface treatment and high-temperature carbonization.

2. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The heavy oil raw material includes one or more of catalytic cracking oil slurry, ethylene tar, atmospheric residue oil and vacuum residue oil.

3. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The components are cut to distill at 5-20 torr, the heavy component A is the fraction with a boiling point greater than 350°C; the light component A1 is the fraction with a boiling point of 200-350°C.

4. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The density of heavy component A at 15℃ is 0.9g / cm 3 above, asphaltene content below 30%, preferably below 25%, saturated content below 20%, preferably below 10%, aromatics content above 50%, preferably above 70%, sulfur content below 1%, preferably below 0.5%, nitrogen content below 0.7%, preferably below 0.4%, residual carbon content 3-20%, preferably 5-15%, most preferably 7-12%.

5. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The asphaltene content in the purified heavy component A is less than or equal to 20%, and the ash content is less than or equal to 10 ppm.

6. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: In step S2, the temperature is raised to a reaction temperature of 360 to 450° C., preferably 400 to 420° C., for pyrolysis reaction at a stirring rate of 50 to 200 r / min and a heating rate of 10 to 30° C. / min, preferably 15 to 25° C. / min. The pyrolysis reaction time is 1 to 15 hours, preferably 6 to 8 hours. The feed ratio of inert gas to purified heavy component A in the pyrolysis reaction is 0.1 L / 1 kg to 0.5 L / kg.

7. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The thermal polymerization reaction temperature in step S3 is 250-350° C., preferably 280-320° C., the reaction time is 2-10 hours, preferably 5-7 hours, the stirring rate is 50-150 r / min, preferably 80-120 r / min, and the reaction pressure is 0.1-0.2 Mpa.

8. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: In step S3, the cross-linking reaction temperature is 80-180° C., preferably 100-120° C., the reaction time is 0.5-3 hours, preferably 1-2 hours, and the stirring speed is 100-300 r / min, preferably 150-200 r / min.

9. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: In step S3, the mass ratio of the coating agent precursor to the catalyst and the cross-linking agent is 1000:1-4:3-10, preferably 1000:1-2:5-7, the catalyst is one of p-toluenesulfonic acid, boron trifluoride, trichloroacetic acid and sulfuric acid, preferably p-toluenesulfonic acid; the cross-linking agent is one or more of terephthalic acid, benzaldehyde, terephthalaldehyde, trioxymethylene and polyformaldehyde.

10. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The vacuum treatment conditions in step S3 are as follows: the vacuum degree is 0.1-100 Pa, preferably 0.5-10 Pa, and the heating temperature is 180-320° C., preferably 250-280° C.

11. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The drying conditions of the carbonaceous mesophase material in step S4 are drying at 80 to 150° C., preferably 90 to 120° C., for 0.1 to 2 hours, preferably 0.5 to 1 hour.

12. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The density of the carbonaceous mesophase material C after drying in step S4 is 1.36-1.4 g / cm 3 , preferably 1.37 to 1.38 g / cm 3 , volatile matter is 10-20%, ash content is less than 0.2%, preferably less than 0.1%; D50 of the crushed carbonaceous mesophase material C is 5-8um, preferably 6-7um; the softening point of the coating agent E is 100-130°C, toluene insoluble matter is 20-30%, quinoline insoluble matter is 0.1-1%, coking value is 45-55%, ash content is 0.01-0.1%, and the D50 of the crushed coating agent E is 1-5um, preferably 2-3um.

13. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The oxygen-containing gas in step S4 is an inert gas containing water vapor or carbon dioxide, the volume ratio of water vapor or carbon dioxide to the inert gas is 1 to 10:100, preferably 4 to 6:100, the gas flow rate of the oxygen-containing element during the modification process is 0.01-0.3 L / min, preferably 0.05-0.1 L / min, the modification time is 5 to 15 hours, preferably 6 to 10 hours, the modification temperature is 550 to 700°C, preferably 620 to 670°C, and the temperature is increased to the modification temperature at a heating rate of 1 to 10°C / min, preferably 5 to 7°C / min.

14. The method for preparing the fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: In step S5, during mixing, the mass ratio of graphite powder F to coating agent E is 100:1 to 100:10, preferably 100:5 to 100:8, and the mixing time is 30 to 60 min, preferably 40 to 50 min; the surface treatment conditions are: under an inert gas flow rate of 0.01-0.3 L / min, preferably 0.05-0.1 L / min, at a heating rate of 1-10 ° C / min, preferably 5-7 ° C / min, heating to 550-700 ° C, preferably 620-670 ° C, and treating for 5 to 15 hours, preferably 6 to 10 hours; the high temperature carbonization conditions are: heating to 1000-1500 ° C, preferably 1200-1300 ° C at a heating rate of 1-7 ° C / min, preferably 3-5 ° C / min, and carbonizing for 1 to 5 hours, preferably 2 to 3 hours.

Citation Information

Patent Citations

  • High-capacity rapid charge graphite negative electrode material and preparation method thereof

    CN109748587A

  • Quick-charging graphite and manufacturing method thereof

    CN111115622A

  • Preparation method of high-magnification quick-charging graphite negative electrode material

    CN112289986A

  • Preparation method of asphalt liquid phase coated modified artificial graphite lithium battery cathode material

    CN103682350A

  • Preparation method of isotropic asphalt for coating and spinning

    CN116925799A